Pelatihan Menulis Karya Ilmiah Menggunakan Referensi Mendeley - Sharon, St Salmah; Jafar, Adindah Novihartina (Universitas Muhammadiyah Malang, 2024)
Purpose – The purpose of this activity is to provide knowledge and skills to lecturers and students in using the Mendeley application to manage citations and references. Design/methodology/approach – This community service activity was carried out based on observations of lecturers and students at STIE Wirabakti who still use the manual method in writing citations and references. Therefore, training is carried out on using the Mendeley application as a reference management tool, which helps lecturers and students work more effectively and efficiently in writing scientific papers. Activities are carried out in three structured stages, including lectures on training materials, practice using applications, and evaluations Findings – The survey results showed a significant increase in the participants' understanding of the use of the Mendeley application in managing citations and scientific work references. This shows the positive benefits and impacts provided by this activity to the participants. Originality/value – Several lecturers and students were involved in this community service activity. The same vision exists between the agency where the activity is carried out and the activity implementing team. This service involves presenters who are Mendeley advisors so that participants can be guided directly in practicing using Mendeley